REPRESENTASI KEKERASAN SEKSUAL TERHADAP PEREMPUAN DALAM FILM VINA: SEBELUM 7 HARI - Muhammad Fuad Hasan; Zahrotus Sa'idah (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This research aims to describe the representation of sexual violence against women in the film Vina: Before 7 Days and its impact on public perception, as well as to contribute to filmmakers in depicting sensitive issues. The urgency of this research lies in the importance of increasing public awareness of the issue of sexual violence which continues to increase. The method used is a qualitative approach with semiotic analysis techniques based on John Fiske's perspective, which focuses on the interaction of signs and audiences in a cultural context. The main data consists of scenes in films that show sexual violence, supported by secondary data from news articles and journals. Data collection techniques include non-participant observation, literature study, and documentation, while analysis is carried out using the Miles & Huberman method, which includes data condensation, data presentation, and drawing conclusions using theoretical triangulation. The results of this research show that the film